Normalized multi-pion Hanbury–Brown–Twiss correlation functions of pion-emitting sources with Bose–Einstein condensation. (3rd October 2019) - Bary, Ghulam; Ru, Peng; Zhang, Wei-Ning
Abstract: Recently, the ALICE collaboration analyzed the three- and four-pion Hanbury–Brown–Twiss (HBT) correlations in Pb–Pb collisions at the Large Hadron Collider. The measured suppressions of three- and four-pion correlations may originate from a substantial coherence of the particle-emitting sources. In this work we investigate the normalized three- and four-pion HBT correlation functions for evolving pion gas (EPG) sources with Bose–Einstein condensation. We find that the intercepts of the normalized correlation functions at zero relative momentum are sensitive to source condensation and particle momentum. The normalized correlation functions in low average-momentum regions of three and four pions decrease with decreasing temperature and increasing particle number of the source, indicating a dependence of the normalized correlation functions on source condensation. However, this dependence becomes weak in an intermediate average-momentum region because particles with high momenta are likely emitted from excited states incoherently in the EPG model, even if the source has a considerable condensation fraction. For a wide momentum range, the normalized correlation functions for low source temperatures are enhanced at larger relative momenta because of a rapid increase of two-pion chaoticity parameter with increasing particle momentum. We hope the significant enhancement of the normalized four-pion correlation function at high relative momentum will be identified through future analyses of experimental data.